Penerapan ReactJs dalam Pengembangan Front-End Aplikasi Komunitas Zeromaterial - Akmal, Fakhirul; Nasrul, Nasrul (LPPM STT Terpadu Nurul Fikri, 2025)
The climate crisis and ongoing environmental degradation have prompted the establishment of ZeroMaterial, a community dedicated to forest conservation and sustainable environmental campaigns. To support the community’s collaborative activities in a digital environment, a responsive and functional web-based platform is essential. This study aims to develop a community-oriented web application using the ReactJS framework to facilitate environmental campaigns and fundraising efforts. The development process follows the Rapid Application Development (RAD) approach, emphasizing rapid iterations and active user involvement at each stage. The main features developed include campaign management and donation functionality. The application was built using ReactJS and Tailwind CSS, and integrated with a REST API as its data provider. Testing results indicate that all features operated correctly, achieving a 100% success rate in Black Box Testing. Furthermore, User Acceptance Testing (UAT) involving 20 respondents yielded an acceptance rate of 94.4%. Although several minor issues were identified related to interface responsiveness, the application is considered feasible and effective in enhancing the collaborative efforts of the ZeroMaterial community in environmental conservation through digital platforms.